1906
DOI: 10.1002/cber.190603904133
|View full text |Cite
|
Sign up to set email alerts
|

Ueber Kobaltimolybdate

Abstract: Die bier zu beschreibenden >Kobaltimolybdate< unterscheiden sich von d m Iangst bekannten Kobaltomolybdaten dadurch, dass sie, mit Chlorwasserstoffsaure gekocht, Chlor entwickeln, also disponiblen Sauerstoff enthalten. Sie zeichnen sich durch eine prachtvoll g r i i n e bis s c b w a r z g r i i n e Farbung aus und bilden sich, wenn man entweder Gernenge yon Kobaltoact tat und Ammonium-oder Kalium-Paraniolybdat (3 R2 0, 7 Moo3) mit Persulfat oder Wasserstoffperoxyd hehandelt, oder wenn man auf Kobaltoacetat Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1908
1908
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…24 Crystal structures of 1 and 2 Single-crystal X-ray crystallographic analyses reveal that the heteropolymolybdate ijCo 2 Mo 10 H 4 O 38 ] 6− in compounds 1-4 is a typical Evans-Showell type polyoxoanion. The polyoxoanion ijCo 2 Mo 10 H 4 O 38 ] 6− was first prepared by Friedheim and Keller in 1906, 25 and was structurally determined as its ammonium salt by Evans and Showell in 1969. 15 The structure of ijCo 2 Mo 10 H 4 O 38 ] 6− can be deduced from the planar Anderson ion ijCoMo 6 H 6 O 24 ] 3− by removing one {MoO 5 } group from each of two ijCoMo 6 H 6 O 24 ] 3− ions, turning one ~45°around the anionic equatorial plane and joining them so that the two CoO 6 octahedra share an edge.…”
Section: Synthesismentioning
confidence: 99%
“…24 Crystal structures of 1 and 2 Single-crystal X-ray crystallographic analyses reveal that the heteropolymolybdate ijCo 2 Mo 10 H 4 O 38 ] 6− in compounds 1-4 is a typical Evans-Showell type polyoxoanion. The polyoxoanion ijCo 2 Mo 10 H 4 O 38 ] 6− was first prepared by Friedheim and Keller in 1906, 25 and was structurally determined as its ammonium salt by Evans and Showell in 1969. 15 The structure of ijCo 2 Mo 10 H 4 O 38 ] 6− can be deduced from the planar Anderson ion ijCoMo 6 H 6 O 24 ] 3− by removing one {MoO 5 } group from each of two ijCoMo 6 H 6 O 24 ] 3− ions, turning one ~45°around the anionic equatorial plane and joining them so that the two CoO 6 octahedra share an edge.…”
Section: Synthesismentioning
confidence: 99%
“…Even if interest in compounds based on Anderson structure is maturing in the literature, only a few works deal with the dimeric HPA Co 2 Mo 10 O 38 H 4 6-, this anion being always associated with the ammonium countercations. Friedheim and Keller 10 first showed that a secondary product with the ratio Co/Mo ) 0.5 is formed during the synthesis of the ammonium salt of CoMo 6 O 24 H 6 4from a solution containing cobalt(II), AHM, and an oxidizing agent. Tsigdinos 11 12 However, these authors specify that from the initial solution two crystallographic forms of ammonium salts are obtained simultaneously, namely, form A and form B, and only the latter form was crystallographically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The support was preliminary loaded with various amounts of cobalt using the aqueous solution of Co(NO 3 ) 2 , in order to increase the ratio Co/Mo = 0.09 occurring in the initial salt (NH 4 ) 3 Co(OH) 6 [17]. Impregnation with the salt was also performed in a vacuum evaporator at 70°C then the impregnated support was dried 4 h at 105°C and calcined 2 h at 350°C.…”
Section: Catalyst Preparationmentioning
confidence: 99%